2016
DOI: 10.1590/0100-67622016000500018
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation and Morphological Aspects of Four Wood Species Used in Lumber Industry

Abstract: -The aim of this work was characterize four wood waste samples from lumber industry in order to obtain previous information about structure and properties of wood before use it as a biofuel or as reinforcement in composite formulations. The influence of wood components on the thermal degradation stability of different wood species has been investigated using thermogravimetry, differential scanning calorimetry and scanning electron microscopy. Four wood species, Eucalyptus grandis (EUG), Pinus elliottii (PIE), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…Figure 7a shows that all composites experienced an increase in luminescence or whitening (L index) along the 12 months of exposure, the composites without CA presented higher whitening, about 133% in the first six months and 180% at the end of 12 months of exposure that continuous increase, as shown in Figure 7c, the composites showed loss of color from brown to whitish (increase of L), this indicates that the climatic conditions solar radiation and rainfall produced the whitening in the composites and possible leaching of the extractives. According to Poletto et al [55], the chemical composition of the extractives influences the color of the wood, and the removal of these components causes whitening. The composites without AC present higher whitening, with more fractures, along of exposure time; while the coupled composites showed lower L index, less intense whitish tone at the end of 12 months of exposure, the PP/BF/CI composites show slightly more stable surfaces than the PP/BF/MA composites, this behavior can also be verified in the micrographs, in general they are results coherent with the mechanical and thermal properties.…”
Section: Optical Analysis: Luminescence and Glossmentioning
confidence: 99%
“…Figure 7a shows that all composites experienced an increase in luminescence or whitening (L index) along the 12 months of exposure, the composites without CA presented higher whitening, about 133% in the first six months and 180% at the end of 12 months of exposure that continuous increase, as shown in Figure 7c, the composites showed loss of color from brown to whitish (increase of L), this indicates that the climatic conditions solar radiation and rainfall produced the whitening in the composites and possible leaching of the extractives. According to Poletto et al [55], the chemical composition of the extractives influences the color of the wood, and the removal of these components causes whitening. The composites without AC present higher whitening, with more fractures, along of exposure time; while the coupled composites showed lower L index, less intense whitish tone at the end of 12 months of exposure, the PP/BF/CI composites show slightly more stable surfaces than the PP/BF/MA composites, this behavior can also be verified in the micrographs, in general they are results coherent with the mechanical and thermal properties.…”
Section: Optical Analysis: Luminescence and Glossmentioning
confidence: 99%
“…Also is observed a difference in the composite ash content, where before exposure there was a greater amount, and after 8 and 12 months it had a pronounced loss, which indicates that the composites underwent complete leaching of inorganic salts from the eighth month of exposure. A study of different wood species found that the degradation of hemicellulose takes place between 170-380 °C, cellulose between 280-400 °C and the lignin begins at around 170 °C and extending above 600 °C [26]. The EVA copolymer suffers by being a two-step degradation: the first at about 330-450 °C, which is where occurs the degradation of the vinyl acetate and the second in the range of 450-520 °C which degrades the olefin part of the copolymer.…”
Section: Influence Of Natural Ageing On the Morphology Changesmentioning
confidence: 99%
“…The TGA and DSC thermogram of rice husk samples subjected to different treatment methods are shown in Figures 4 and 5. From the DSC thermograms obtained (Figure 5), the samples had very distinct endothermic peaks at the selected working range (Cengiz, Kaya, and Bayramgil 2017) change occurs at 70-100°C due to evaporation of water and the second endothermic reaction which shows the degradation of hemicellulose structure, which is usually observed between 180°C and 300°C (Poletto 2016). Of all the samples analyzed, only alkali-treated rice husks had a small peak at this region, which is an indication of the presence of residual hemicellulose.…”
Section: Thermal Analysismentioning
confidence: 98%
“…Of all the samples analyzed, only alkali-treated rice husks had a small peak at this region, which is an indication of the presence of residual hemicellulose. The degradation reaction of cellulose starts at 300°C and continues to 400°C with a maximum mass loss occurring at 351, 339 and 305°C for alkali-treated rice husks (ATRH), rice husks cellulose (RHCE), mechanically treated (MTCE) and ultrasonicated cellulose (USCE) respectively (Poletto 2016;Poletto, Ornaghi, and Zattera 2014). Generally, cellulose derived from natural fibers has high thermal stabilities due to αcellulose of lignocellulosic structures (Cengiz, Kaya, and Bayramgil 2017).…”
Section: Thermal Analysismentioning
confidence: 99%